NormalizaNormalisasi Gratifikasi dalam Pendidikan Dasar dan Menengah: Strategi Pencegahan Berbasis Ekosistem Berintegritastion of Gratification in Primary and Secondary Education: An Ecosystem-Based Prevention Strategy with Integrity - Andes, Andes Robensyah (University Of Bengkulu Law Journal, 2026)
The normalization of gratification in primary and secondary education in Indonesia indicates that corrupt practices do not always appear in large-scale forms, but often originate from seemingly minor and socially accepted actions, such as giving gifts to teachers, informal levies, and compromises in academic grading. This phenomenon reflects an ambiguity between the culture of gift-giving and gratification that has the potential to create conflicts of interest and weaken the integrity of education. This study aims to analyze the dynamics of gratification normalization as an embryo of a corrupt culture and to formulate ecosystem-based prevention strategies toward integrity-driven education. The research employs a socio-legal approach with a qualitative descriptive-analytical method to understand the relationship between legal norms, culture, and social practices within the education sector. The findings reveal that the normalization of gratification is influenced by cultural rationalization, the socio-economic pressures faced by families, weak governance, and the lack of alignment between legal norms and social norms. Empirical data from the Komisi Pemberantasan Korupsi through the Education Integrity Assessment Survey indicate that tolerance toward the practice of giving gifts to educators remains relatively high. This condition has the potential to foster habituation and the reproduction of permissive values toward misconduct from an early age.This study proposes a conceptual model of ecosystem-based prevention involving schools, families, communities, and the government through value transformation, governance reform, social participation, and cross-sector policy integration. This systemic approach is expected to strengthen educational integrity and prevent the sustained reproduction of corrupt cultural practices.